Analisis Penerapan Metode HIRADC Sebagai Upaya Pengendalian Risiko Bahaya Pada Laboratorium Kalibrasi PT XYZ - Gufron, Achmad; Rusindiyanto (Jurnal Serambi Engineering, 2025)
PT XYZ as a company engaged in manufacturing and maritime engineering, has a calibration laboratory with various potential hazard risks. Thus, risk control efforts are needed to minimize the negative impact on occupational safety and health (K3). This study aims to evaluate the potential risk of hazards in the Dimensional, Pressure, and Electrical Calibration Laboratory using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method at PT XYZ. The data used in this study are primary data conducted in three calibration laboratories at PT XYZ. The identification results show the existence of various potential risks such as skin irritation due to chemicals, health problems due to extreme conditions, and physical fatigue due to improper work positions. Based on the analysis, it was found that the risk level of the electrical calibration laboratory was classified as high risk with 67%, the pressure calibration laboratory was classified as moderate risk with 60%, and the dimensional calibration laboratory was classified as moderate risk with 60% before control. After the implementation of risk control through the control hierarchy, the risk level in several laboratories decreased to low or moderate. The results of this study indicate that the HIRADC method is effective in identifying and controlling hazard risks, as well as the importance of implementing appropriate control measures to increase the risk level.